2015
DOI: 10.1007/s10880-015-9437-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Avoidance and Rumination in Parents of Children on Cancer Treatment: Relationships with Posttraumatic Stress Symptoms and Symptoms of Depression

Abstract: We conducted a cross-sectional survey study to investigate whether there is a relationship between experiential avoidance (EA), rumination, post-traumatic stress symptoms (PTSS), and symptoms of depression, in parents of children on cancer treatment. Data from 79 parents (55 mothers) of 79 children with a median of three months since their cancer diagnosis were included in cross-sectional analyses. EA and rumination were positively correlated with PTSS and symptoms of depression. EA and rumination did not prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
3
22
0
5
Order By: Relevance
“…Mothers stated that they spent the majority of their time with the ill child, either in hospital or at home and therefore having no time for their basic needs. Findings in the current study are similar to those of Cernvall et al (2015), who investigated depression among 79 parents of children with cancer and reported that depression symptoms were very prevalent. Additionally, parental depression when having a child with cancer was also reported in a study in China (Chen et al, 2014).…”
Section: Depressionsupporting
confidence: 88%
“…Mothers stated that they spent the majority of their time with the ill child, either in hospital or at home and therefore having no time for their basic needs. Findings in the current study are similar to those of Cernvall et al (2015), who investigated depression among 79 parents of children with cancer and reported that depression symptoms were very prevalent. Additionally, parental depression when having a child with cancer was also reported in a study in China (Chen et al, 2014).…”
Section: Depressionsupporting
confidence: 88%
“…Many parents struggling with their child's cancer are found to show symptoms of depression and posttraumatic stress disorder (PTSD), which mainly comprises intrusions in the form of recurring images, dreams and trauma-related thoughts, arousal indicating increased alertness and fear, as well as avoidance shown by way of attempts to discard thoughts and emotions connected with the experienced event [2][3][4]. Research mentioned by Baran [5] indicates that 95% of mothers whose children got cancer showed the presence of symptoms of intrusion, half of them showed symptoms of arousal and 40% symptoms of avoidance.…”
Section: Purpose Cancer As Traumatic Experiencementioning
confidence: 99%
“…U wielu rodziców zmagających się z chorobą nowotworową dziecka stwierdza się występowanie objawów depresji i stresu pourazowego (posttraumatic stress disorder -PTSD), na który składają się przede wszystkim intruzje, wyrażają-ce powracające obrazy, sny i myśli związane z traumą, pobudzenie, wskazujące na wzmożoną czujność i wystę-powanie lęku, oraz unikanie, przejawiające się próbami pozbycia się myśli i emocji związanych z doświadczonym zdarzeniem [2][3][4]. Badania przytaczane przez Baran [5] wskazują, że 95% matek, których dzieci zachorowały na raka, ujawniło występowanie objawów intruzji, połowa z nich objawy pobudzenia, a 40% unikania.…”
Section: Cel Choroba Nowotworowa Jako Doświadczenie Traumatyczneunclassified
“…Tego typu doświadczenia pociągają za sobą wiele niekorzystnych następstw, przejawiających się w różnych obszarach funkcjonowania. U wielu rodziców zmagających się z chorobami somatycznymi dziecka, w tym nowotworowymi, stwierdza się występowanie objawów depresji i stresu pourazowego [2][3][4].…”
Section: Wstępunclassified